Assessment of farmers' knowledge, attitudes and practices toward brucellosis in Sibu Sire District, East Wallaga Zone of Western Oromiya, Ethiopia - Begna Bulcha; Monenus Etefa (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Brucellosis is a contagious zoonotic disease transferred from sick animals to humans and endemic in Eastern Africa and other countries. The objective of this study was to assess the extent of the knowledge and attitudes relating to brucellosis at the human-animal interface and identify practice at the farm and household level that poses a risk for human infection at the study site. By cross-sectional study design, a total of 120 participants were involved in assessing Knowledge, Attitude, and practice (KAP) toward the disease. From the study, about 20% of respondents knew the disease, out of which 75% heard about it from a veterinary service. Nearly, 79% and 75% understood that the disease can be transmitted between cattle and from cattle to humans respectively. About 54.2% handle placental membranes and aborted fetuses with bare hands. Of the total respondents, 5.8% and 38.3% have had good knowledge and good practice scores respectively. Educational level, with illiterate less, knew, highly influences both knowledge (p = 0.01) and practice (p = 0.018) of the respondents. Males (p = 0.006) had a good practice, which was statistically significant. This indicates that an awareness creation campaign is important so as to equip the farmers in the study areas with knowledge of the disease and to change their malpractice in order to protect themselves from brucellosis.